Strategies for Enhancing the Quality and Effectiveness of Ideological and Political Education in Colleges and Universities under the Background of Chinese Modernization - Wang, Yutong (Education Insights, 2026)
Recent strategic frameworks have explicitly proposed advancing societal development through Chinese modernization, charting the course and defining the historical mission for moral and political education (MPE) in higher education institutions. As an essential component of the modern university system, MPE undertakes the fundamental task of cultivating virtue and nurturing talent, serving as the principal channel for consolidating guiding philosophical principles within the academic sphere. Currently, challenges persist in MPE regarding outdated content supply, monotonous teaching methodologies, insufficient collaborative mechanisms between specialized courses and MPE programs, and evaluation systems that over-emphasize memorization while neglecting value identification. These issues fail to fully align with the requirements of modernization for cultivating well-rounded individuals. Based on an in-depth analysis of the inherent compatibility between Chinese modernization and the improvement of MPE quality, this paper dissects existing dilemmas from a problem-oriented perspective. It proposes specific enhancement strategies across five interconnected dimensions: systematically optimizing educational content by integrating distinctive modernization features; innovating teaching models through case-based, inquiry-based, and digitally-blended courses; strengthening faculty development via collaborative lesson preparation and field research; improving collaborative education mechanisms to realize synergy across the broader curriculum; and refining a multi-dimensional evaluation system combining process and outcome assessments. Ultimately, only through systematic, whole-process transformation can universities effectively promote the high-quality development of MPE and cultivate high-caliber talents capable of contributing to the modernization drive and long-term societal advancement.